Synthesis of Triptycene-Substituted Azapentacene and Azahexacene Derivatives - Biegger, Philipp; Tverskoy, Olena; Rominger, Frank; Bunz, Uwe H. F. (Chemistry - a European journal, 2016)
Abstract We describe the synthesis and characterization of novel iptycene-substituted azaacenes by using either a classic condensation route (diamine plus ortho-quinone) and/or a Pd-catalyzed coupling of an aromatic diamine with an aromatic dihalide. The attachment of an iptycene unit leads to a significant blueshift (15?nm) in the UV/Vis spectra of these azaacenes. The iptycene unit stabilizes a hexaazahexacene with a ?max?abs of 833?nm. By employing 5,6-diamino(benzothiadiazole) as a synthon for tetraaminobenzene, we could prepare the symmetrical bis-triptycene-substituted tetraazapentacene in high yields.
Gesehen am 11.05.2020